The application of bone morphogenetic proteins in medicine, dentistry, sport and rehabilitation: A review of literature - ALEKSANDRA JARON (Baltic Journal of Health and Physical Activity, 2020)
Bone tissue is a mineralized structure with a complicated metabolism and due to its mechanical functions its structure must be adapted to the bone function. The BMP protein group stimulates the formation of bone and cartilage and influences numerous non-osteogenic processes. As a result of their osteogenic effect, BMP proteins are used in numerous areas of medicine, including dentistry and orthopaedics, as well as sport and rehabilitation. The publications used in this paper were sourced from the PubMed and the Google Scholar databases. The index entries used to search the databases included BMP, bone morphogenetic proteins, medicine, dentistry and sport. BMP proteins have a wide range of applications, particularly in dentistry and sports medicine. The study demonstrates that autogenous material is the best for bone regeneration as a result of using resources of BMP proteins and bone-forming cells. Undeniably, the condition of the patient's body undergoing treatment with BMP is not without significance. According to the authors of the article, all applications and treatment options with the use of BMPs are yet to be known. Perhaps further development of medicine will make their discovery possible.